2004
DOI: 10.1002/ps.929
|View full text |Cite
|
Sign up to set email alerts
|

Chemical residues and bioactivity of tebufenozide applied to apple foliage

Abstract: Tebufenozide, an insect growth regulator that acts as an ecdysone agonist, was applied at recommended label rate to apple trees in August 1997 and May 1998. Foliar residues were determined by high-performance liquid chromatography from samples collected 2, 24, 48 and 96 h post-spray, and at weekly intervals thereafter for 9 weeks in 1997 and 11 weeks in 1998. Foliage sampled at the same times was used in bioassays to determine residual toxicity to first-instar obliquebanded leafrollers, Choristoneura rosaceana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The long activity period of methoxyfenozide observed in this study was similar to that found with other diacylhydrazines and IGRs. It seems that this residual activity is based on persistence of insecticide residue on treated plants and not on sublethal effects of insecticide applied against a previous generation (Smirle et al 2004, Borchert et al 2005, Pavan et al 2005. Therefore, residue dilution on plant surface by factors such as temperature, UV light, rainfall, and plant growth will interact with pest phenology to determine the duration of efÞcacy of methoxyfenozide.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The long activity period of methoxyfenozide observed in this study was similar to that found with other diacylhydrazines and IGRs. It seems that this residual activity is based on persistence of insecticide residue on treated plants and not on sublethal effects of insecticide applied against a previous generation (Smirle et al 2004, Borchert et al 2005, Pavan et al 2005. Therefore, residue dilution on plant surface by factors such as temperature, UV light, rainfall, and plant growth will interact with pest phenology to determine the duration of efÞcacy of methoxyfenozide.…”
Section: Discussionmentioning
confidence: 98%
“…Residual half-life of tebufenozide concentration on apple (Malus spp.) leaves was 7.2 and 36.3 d in May and August, respectively, and the estimated time needed to decrease bioactivity by 50% was 36.6 and 18.7 d, respectively (Smirle et al 2004). The long residual activity of diacylhydrazine insecticides indicates that the management strategy traditionally used with conventional insecticides, such as multiple insecticide applications throughout the season, could be modiÞed.…”
mentioning
confidence: 96%
“…It is well known that leaf age and environmental conditions influence the persistence, and consequently the efficacy, of any chemical insecticide 30, 31. In particular, photolysis is the main responsible factor of a rapid breakdown of spinosad in the environment 13.…”
Section: Discussionmentioning
confidence: 99%
“…The diacylhydrazine insecticide family shows efficacy against lepidopteran larvae in the field and laboratory [6]. Tebufenozide and its methoxylated derivative methoxyfenozide present intrepid activity as agonists or mimic the insect molting hormone 20-hydroxyecdynose by inducing premature, incomplete ecdysis, resulting in the death of the exposed insects [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%